2021
DOI: 10.1002/bit.27692
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics simulation of a compression–perfusion combined bioreactor to predict the mechanical microenvironment during bone metastatic breast cancer loading experiments

Abstract: Incurable breast cancer bone metastasis causes widespread bone loss, resulting in fragility, pain, increased fracture risk, and ultimately increased patient mortality. Increased mechanical signals in the skeleton are anabolic and protect against bone loss, and they may also do so during osteolytic bone metastasis. Skeletal mechanical signals include interdependent tissue deformations and interstitial fluid flow, but how metastatic tumor cells respond to each of these individual signals remains underinvestigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…MLO-Y4-seeded scaffolds received either steady perfusion (0.3 ml/min inlet volumetric flow rate, resulting in 100 μm/s inlet velocity; 1 h per loading bout) or pulsatile perfusion (0.3 ml/min inlet volume applied at 1 Hz) from our bioreactor (Bangalore Integrated System Solutions) ( Fig. 1 B), loading regimes that we previously verified via Computational Fluid Dynamics simulations to be within the physiological range of anabolic mechanical loading [ 34 , 35 ]. Within the bioreactor chamber, each scaffold sits in an individual well (up to 9 per chamber), and is positioned between two sintered metal mesh disks that produce uniform inlet and outlet flows ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MLO-Y4-seeded scaffolds received either steady perfusion (0.3 ml/min inlet volumetric flow rate, resulting in 100 μm/s inlet velocity; 1 h per loading bout) or pulsatile perfusion (0.3 ml/min inlet volume applied at 1 Hz) from our bioreactor (Bangalore Integrated System Solutions) ( Fig. 1 B), loading regimes that we previously verified via Computational Fluid Dynamics simulations to be within the physiological range of anabolic mechanical loading [ 34 , 35 ]. Within the bioreactor chamber, each scaffold sits in an individual well (up to 9 per chamber), and is positioned between two sintered metal mesh disks that produce uniform inlet and outlet flows ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…While we chose this regime based on an initial side-by-side comparison of steady versus pulsatile flow and on steady perfusion being more common in bone tissue engineering studies, future studies should employ unsteady flow. Lastly, a 3D system is more physiological than a 2D one, and we have extensively characterized the interior mechanics of our 3D bone scaffolds that attached cells would ‘feel’ during experimentation via computation modeling [ 34 , 35 , 66 ]. However, it does not mimic the native structure of the lacunar-canalicular network found within bone.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…A few recent research works based on milliscale bioreactors have demonstrated that the combined effect of perfusion and anabolic drugs (e.g., 2-chloro-5-nitrobenzanilide, a PPARγ inhibitor (GW9662), hydrogen sulphide, parathyroid hormone) can enhance collagen deposition and bone mineralization ( Grant et al, 2016 ; Liu et al, 2018 ; Gambari et al, 2019 ; Mondragon et al, 2020 ; Liu et al, 2021 ). Mondragon et al showed that perfused cultures of MSCs on lyophilized bovine collagen type I scaffolds upon which Mg-doped HA nanocrystals nucleated during collagen fibrils self-assembly and treated with GW9662, led to an increased scaffold mineral density and compressive modulus ( Mondragon et al, 2020 ).…”
Section: Perfused Bioreactors For Drug Screening Of Anabolic and Anti-catabolic Drugsmentioning
confidence: 99%